Levels of persistent organic pollutants (POPs) in foods from the first regional Sub-Saharan Africa Total Diet Study. (February 2020) - Vaccher, Vincent; Ingenbleek, Luc; Adegboye, Abimobola; Hossou, Sétondji Epiphane; Koné, Abdoulaye Zié; Oyedele, Awoyinka Dada; Kisito, Chabi Sika K.J.; Dembélé, Yara Koreissi; Hu, Reinwei; Adbel Malak, Inas; Cariou, Ronan; Vénisseau, Anaïs; et al.
Graphical abstract: Highlights: POPs levels in food from Benin, Cameroon, Mali and Nigeria. Representative foods prepared as consumed and pooled before analysis. The highest levels of POPs found in food group "fish" Smoking process suspected to account for specific POPs profiles in fish. PFAS associated to pesticides in smoked fish in Mali. Abstract: For the first time, a multi-centre Total Diet Study was carried out in Benin, Cameroon, Mali and Nigeria. We collected and prepared as consumed 528 typical fatty foods from those areas and pooled these subsamples into 44 composites samples. These core foods were tested for a wide spectrum of POPs, including polychlorinated dibenzo-p-dioxins (PCDDs), polychlorinated dibenzofurans (PCDFs), polychlorinated biphenyls (PCBs), brominated flame-retardants (BFRs), organochlorine compounds (OCs), perfluoro alkyl substances (PFAS) and chlorinated flame retardants (CFRs). The POPs contamination levels were similar or lower than those reported in total diet studies previously conducted worldwide. In most cases, core foods belonging to fish food group presented higher POPs concentrations than the other food groups. Interestingly, we observed a difference in both contamination profile and concentration for smoked fish compared to non-smoked fish. Such finding suggests that the smoking process itself might account for a large proportion of the contamination. Further investigation would require the assessment of combustion materials used to smoke fish as a potential vehicle, which may contribute to the dietary exposure of the studied populations to POPs.